Spectral Animals: Deligny's Autistic Vision and the Presence of the Immortal (Non)Human - Bishop, Graham L. (Contemporary French and francophone studies, 2022)
Citing essays and films by the French experimental educator and writer Fernand Deligny, this article explores how discourses of visibility and invisibility inform comparisons between nonhuman perception and the forms of "vision" attributed to the autism spectrum. Drawing on Derrida's work, I argue that Deligny places both animals and autistic people on the opposite side of a "spectral" threshold in relation to the neurotypical human. These nonnormative subjects "regularly [exceed] all the oppositions between visible and invisible, sensible and insensible" (Derrida 117). In the French language, which translates "autism spectrum disorder" as "le trouble du spectre autistique," this excess (which also pertains to the "spectrum" of the visible) is manifest on a semantic level. The rise of "hauntological" readings informed by Derrida's work on "le spectre" in Spectres de Marx and Échographies de la télévision therefore requires us to locate and to deconstruct the "autistic specter" that poses such "trouble" for literary and medical narrative. What this particular specter "haunts," I argue, is a definition of the human as a subject that possesses, in contrast to nonhuman animals and machines, a unique capacity to create and interpret narrative.